IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT AND THE RAHMATAN LIL ALAMIN STUDENT PROFILE IN ARTS AND CULTURE AND PRACTICE COURSES IN GRADE IV OF MIN 3 MATARAM - Rodiatul Jannah (JOETAL: Journal of Education, Teaching and Learning, 2026)
The purpose of this study is to describe the implementation of the Pancasila Student Profile Strengthening Project and the Rahmatan lil Alamin Student Profile in Arts, Culture, and Crafts subjects in Grade IV of MIN 3 Mataram City, as well as the supporting and inhibiting factors in implementing  in Arts, Culture, and Crafts subjects in Grade IV of MIN 3 Mataram City. This study used a qualitative approach and was descriptive in nature. Data collection techniques used in this study included interviews, observation, and documentation. This study employed data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. Data validity techniques used in this study included extended observation, triangulation, and reference coverage. The results showed (1) The implementation of  in Arts, Culture, and Crafts subjects in Grade IV of MIN 3 Mataram City involved forming a facilitator team, identifying educational unit readiness, designing dimensions, themes, and time allocation, compiling teaching modules, and designing project reporting strategies. (2) Supporting factors include providing facilities, planning time allocation, and active participation. Meanwhile, inhibiting factors include the lack of socialization of the  (Public Education and Training Program), differences in student characteristics, and a lack of accompanying teachers.